ANALISIS RANTAI PASOKAN SAYURAN DI PASAR INDUK KOTA PANGKALPINANG - Yuni Kartika; Yudi Sapta Pranoto; Fournita Agustina (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
The market is the meeting place between the trader and the buyer so that the process of distributing products and services are often performed on the market both traditional and modern market. Distribution of products is usally done directly by distributors with vegetable trades so that there is a difference in price and volume on products sold by the vegetable traders. This study aims to count the volume of vegetables based on incoming types, as well as analyze the factors that influence the level of vegetables volume which come into Pasar Induk Pangkalpinang. This research was carried out from December 2017 up to January 2019 in Pasar Induk Pangkalpinang. The method used in this research was case study method. The sampling method was census method with 48 sample consist of 6 wholesalers, 2 distributors, and 40 retailers. The data analysis method used is qualitative descriptive and multiple linier regression analysis. The result shows The volume of vegetables supply in Pasar Induk Pangkalpinang based on the types, those are: 114.750 kgs of leafy greenspermonth, 137.400kgs of fruits per month, 450kgs of flowery veggies per month, 17.400 kgs of seed and nuts per month, and also 111.200 kgs of tube rous roots per month. The factors influencing the level of vegetable supply volume, it is only 6 variables among7 estimator variables that statistically influenceon 5% level, which is sig < 0.05, price (X1), profit (X2), transportation (X4), availibility of vegetable (D1), quality of vegetable (D2) and supplier area (D3).